Method for producing composite copper foil and composite copper foil obtained thereby

By depositing an amorphous ternary alloy peeling layer of nickel, molybdenum and tungsten on the carrier foil and performing acid washing, the problem of insufficient peeling strength of composite copper foil under low-temperature lamination conditions is solved, and the effect of high peeling strength and compliance with REACH regulations is achieved.

CN120225731APending Publication Date: 2025-06-27COPPER FOIL LUXEMBOURG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380079191.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-22
Filing Date
2023-11-29
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The prior art is difficult to produce composite copper foils with high peel strength under low temperature lamination conditions, and the traditional method of using hexavalent chromium is limited by REACH regulations.

Method used

An amorphous ternary alloy release layer is deposited on the carrier foil using an acidic electrolyte containing nickel, molybdenum and tungsten, and the release layer is washed by an acid washing solution to form a composite copper foil suitable for low-temperature lamination.

Benefits of technology

During low-temperature lamination, the produced composite copper foil has a peel strength of 30-120N/m, which is suitable for low-temperature lamination processes and comply with REACH regulations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120225731A_ABST
    Figure CN120225731A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a peelable composite copper foil, comprising:-providing a carrier foil; depositing a release layer comprising a ternary alloy of nickel, molybdenum and tungsten on the carrier foil using an acidic electrolyte comprising nickel, molybdenum and tungsten, said release layer being an amorphous layer; washing the exposed side of the release layer on the carrier foil with a washing solution having a pH of 2.5-4.5; and electroplating an ultra-thin copper foil on the release layer. The present invention also relates to the obtained composite copper foil comprising a carrier foil, a release layer, and an ultrathin copper foil in this order, in which the release layer comprises a ternary alloy of nickel, molybdenum, and tungsten formed as an amorphous layer, and in which the release layer has a peel strength of 30-120 N / m after lamination at 170 DEG C for 1 hour.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of composite copper foils, and more particularly, to composite copper foils having a release layer and methods for their production. Background Art

[0002] With the miniaturization of electronic devices, ultra-thin copper foils with a thickness of about 5 μm or less have been used as electronic materials for printed circuit boards (PCBs). Such ultra-thin copper foils are generally not self-supporting and are thus not easy to use. To solve such problems, composite copper foils in which an ultra-thin copper layer is attached to a carrier (support) layer are being used.

[0003] Composite foils are generally divided into two categories: namely, foils with a peelable carrier and foils with an etchable carrier. Briefly, the difference between these two composite foils lies in the method of removing the carrier layer. In peelable composite foils, the carrier layer is removed by peeling, while in etchable composite foils, the carrier layer is removed by etching.

[0004] Peelable composite foils are generally more preferred than etchable composite foils because they can be used to prepare copper-clad laminates more simply and precisely. In fact, the chemical etching time of the carrier is very long - due to its relatively significant thickness - requiring multiple changes of the etching bath and resulting in a rough surface. In addition, since the ultra-thin copper layer must not be etched, it limits the choice of the carrier layer.

[0005] Therefore, peelable composite foils are easier to use than etchable foils. However, a recurring problem with traditional peelable composite foils is that it is difficult to control their peel strength, i.e., the force required to separate the carrier foil from the ultra-thin copper foil after lamination.

[0006] Traditional composite copper foils and their production methods are known from US 3998601, in which the carrier and the functional foil are joined by a release layer formed using an electroplating bath containing hexavalent chromium. However, such composite copper foils are subject to the REACH regulation and will no longer be able to be produced after 2023 due to the use of hexavalent chromium.

[0007] To overcome this limitation, alternative manufacturing processes have been developed. For example, document WO 2020 / 173574A1 discloses a method for producing a peelable composite copper foil without using chromium. The release layer is formed as an amorphous layer of a binary or ternary nickel alloy. Such a composite copper foil has a low peel strength during lamination, typically 5 - 30 N / m, and is very suitable for certain markets where the composite foil is laminated at a relatively high temperature (usually about 220 °C), and the carrier layer is peeled off after this lamination step. It can be noted here that during the lamination process, the applied temperature has the effect of improving the bond between the carrier layer and the functional foil. That is, during lamination, the temperature will increase the initially low peel strength, thereby improving the stability of the assembly and avoiding the accidental separation of the peelable foil.

[0008] In contrast, in Europe, the industry typically uses processes involving lamination at a lower temperature (usually below 180 °C). Tests carried out using the composite copper foil of WO 2020 / 173574 A1 have shown that after low-temperature lamination, the peel strength is close to zero. Therefore, satisfactory adhesion of the carrier layer cannot be ensured, and thus it cannot play a protective role during the subsequent processing of the copper-clad laminate. Therefore, the composite copper foil disclosed in WO 2020 / 173574 A1 is not suitable for low-temperature lamination processes.

[0009] Object of the invention

[0010] The object of the present invention is to provide a method for producing a composite copper foil with a high peel strength suitable for low-temperature lamination, while the method complies with REACH regulations. Summary of the invention

[0011] To achieve the above object, the present invention proposes a method for producing a composite copper foil comprising a carrier foil, a release layer, and an ultra-thin copper foil that can be peeled off from the carrier foil, the method comprising:

[0012] - Providing a carrier foil;

[0013] - Depositing a release layer of a ternary alloy comprising nickel, molybdenum, and tungsten on one side of the carrier foil using an acidic electrolyte comprising nickel, molybdenum, and tungsten, the release layer being an amorphous layer;

[0014] - Washing the exposed side of the release layer on the carrier foil with a washing solution having a pH of 2.5 - 4.5;

[0015] - Electroplating an ultra-thin copper foil on the release layer.

[0016] The method of the present invention allows the production of composite copper foils having a peel strength in the range of 30 - 20 / m, preferably 40 - 120 N / m, when laminated at low temperature. It should be understood that the peel strength can be adapted to a given application. Thus, in embodiments, the peel strength can be in the range of 40 up to 80, 90 or 100 N / m, and in other embodiments, the peel strength can be in the range of 70 or 80 up to 120 N / m. In other embodiments, the peel strength can be in the range of 70 - 90 N / m.

[0017] As used herein, the term "peel strength" refers to the force required to separate the carrier foil from the ultra-thin copper foil. Since the bonding between the ultra-thin copper foil and the carrier foil is due to the release layer, the peel strength may also be referred to in the art as "release strength". In practice, the peel strength is typically measured after lamination.

[0018] It should be understood that the inventors have found that a washing step applied to the exposed side of the release layer allows for controlled oxidation of the release layer surface and thereby allows for control of the peel strength of the composite copper foil. The bulk of the release layer is not affected by the washing step (only the surface). Since the ultra-thin copper foil is formed on the washed side of the release layer, oxides of the components / elements of the ternary alloy will be present at the interface with the ultra-thin copper foil, which will affect / control the peel strength.

[0019] Compared with the composite copper foil of WO 2020 / 173574 A1, the inventors surprisingly found that the washing step allows the peel strength to be increased to a higher range while the carrier foil remains peelable during the lamination step at temperatures up to 170°C.

[0020] In other words, the present invention is based on the inventors' discovery that a specific method step comprising washing the release layer with an acidic washing solution can produce a composite copper foil suitable for lamination at low temperature, exhibiting a peel strength of 30 - 120 N / m after lamination at 170°C for 1 hour.

[0021] The present invention relies on using a washing solution to wash the release layer to control the peel strength of the composite copper foil. In fact, the inventors have found that washing the release layer with a washing solution results in the formation of oxides on the release layer surface. The presence and content of the oxides will regulate (i.e., control) the peel strength of the composite copper foil. Thus, the peel strength, i.e., the bonding force between the carrier and the ultra-thin copper foil, can be controlled by fine-tuning the washing step and thereby controlling the formation of oxides.

[0022] In addition, since the release layer is formed as an amorphous alloy layer, it presents a smooth surface with substantially no irregularities caused by grain boundaries, thereby preventing the formation of structural defects such as, for example, pinholes in the foil deposited thereon. In other words, forming the release layer as an amorphous layer allows for the production of a composite copper foil free of structural defects such as, for example, pinholes.

[0023] In an embodiment, the pH of the washing solution is 2.5 - 4.0, preferably 2.5 - 3.5. According to the same or different embodiments, the washing solution comprises water and any suitable acid, preferably an inorganic acid such as H2SO4, HCl, etc.

[0024] In a preferred embodiment, washing the exposed side of the release layer (i.e., the washing step) comprises spraying the washing solution onto the exposed side of the release layer and / or immersing the carrier foil having the release layer deposited thereon in the washing solution. More preferably, the washing step sequentially comprises spraying the washing solution onto the exposed surface of the release layer, immersing the carrier foil with the release layer in the washing solution, and spraying the washing solution onto the exposed side of the release layer again.

[0025] In an embodiment, the washing of the exposed side of the release layer (i.e., the washing step) is carried out for a period of 10 - 50 seconds, preferably 10 - 30 seconds. In embodiments where the washing step comprises spraying the washing solution and immersing in the washing solution, the immersion is preferably carried out for a time equivalent to 20% - 25% of the total time of the washing step.

[0026] In an embodiment, the washed release layer can be wiped by passing through rotating rollers, such as nip rollers.

[0027] According to the same or other embodiments, the washed release layer can be placed in air for 10 - 40 seconds to dry the washed release layer.

[0028] According to the same or other embodiments, the acidic electrolyte contains nickel at a concentration of 5.0 - 9.0 g / L, preferably 7.0 - 9.0 g / L, more preferably 7.5 - 8.5 g / L, molybdenum at a concentration of 5.0 - 9.0 g / L, preferably 5.0 - 7.0 g / L, more preferably 5.5 - 6.5 g / L, and tungsten at a concentration of 1.0 - 5.0 g / L, preferably 2.0 - 4.0 g / L, more preferably 2.5 - 3.5 g / L.

[0029] The inventors have surprisingly found that electrodepositing the release layer from an electrolytic bath having such a specified composition in combination with the washing step is particularly effective in achieving the desired release strength during low-temperature lamination.

[0030] In an embodiment, electroplating the ultra-thin copper foil comprises:

[0031] Electroplating a first copper layer directly on the release layer using an alkaline copper electrolyte; and

[0032] Electroplating a second copper layer on the first copper layer using an acidic copper electrolyte.

[0033] Preferably, the alkaline bath may contain pyrophosphate ions, cyanate ions, and / or amidosulfonate ions.

[0034] According to another aspect, the present invention relates to a composite copper foil comprising a carrier foil, a release layer, and an ultra-thin copper foil in sequence, wherein the composite copper foil has a peel strength of 30 - 120 N / m after being laminated at 170 °C for 1 hour.

[0035] In an embodiment, the peel strength may be in the range of 40 to up to 80, 90, or 100 N / m, and in other embodiments, the peel strength may be in the range of 70 or 80 to up to 120 N / m. In other embodiments, the peel strength may also be in the range of 70 - 90 N / m.

[0036] The release layer comprises an amorphous ternary alloy of nickel, molybdenum, and tungsten.

[0037] In an embodiment, the release layer includes nickel in the form of an oxide, wherein nickel in the +II oxidation state accounts for at least 30 wt% of the total surface nickel. In an embodiment, the amount of Ni(+II) may be 30 wt% - 50 wt% of the total surface nickel. The first test shows that this proportion of nickel in the oxidized form allows for the production of copper foils with the desired peel strength properties.

[0038] As described above regarding the method of the present invention, the present invention is based on the discovery of the inventors that the presence of oxides of the components / elements of the ternary alloy (especially nickel in the form of an oxide) at the interface with the ultra-thin copper foil affects / controls the peel strength of the composite copper foil.

[0039] The presence and amount of nickel in the form of an oxide (i.e., nickel oxide) regulate (i.e., control) the peel strength of the composite copper foil. Therefore, the peel strength, i.e., the bonding force between the carrier and the ultra-thin copper foil, can be controlled by fine-tuning the amount of nickel oxide.

[0040] Furthermore, since the release layer comprises an amorphous alloy layer, it presents a smooth surface, substantially free of irregularities caused by grain boundaries, thereby preventing the formation of structural defects such as, for example, pinholes in the foil deposited thereon. In other words, the release layer comprising an amorphous layer renders the composite copper foil free of structural defects such as, for example, pinholes.

[0041] Any other advantages described regarding the method of the present invention apply to the composite copper foil of the present invention with necessary modifications in details.

[0042] According to the same or other embodiments, the thickness of the release layer is 5-50 nm, preferably 30-50 nm, more preferably 35-50 nm.

[0043] Advantageously, depending on the intended application of the composite copper foil, the thickness of the ultra-thin copper foil can be 0.5-10 μm, specifically 5-9 μm.

[0044] According to still another aspect, the present invention relates to a copper-clad laminate comprising a substrate having a resin and the disclosed composite copper foil, wherein the ultra-thin copper foil is laminated on the exposed surface of the substrate.

[0045] wherein the resin of the substrate has a Tg of less than 170 °C, and

[0046] wherein the release strength of the release layer after lamination at 170 °C for 1 hour is 30-120 N / m.

[0047] Advantageously, the composite copper foil is produced by the method according to the present invention, or the composite copper foil is the composite copper foil according to the present invention.

[0048] What has been said about the advantages and embodiments of the composite copper foil of the present invention applies, mutatis mutandis, to the copper-clad laminate of the present invention.

[0049] As used herein, the term "amorphous" refers to a situation where a broad diffraction peak appears when measured by grazing incidence X-ray diffraction (GIXRD), or a situation where a hollow pattern appears at the peak when measuring electron beam diffraction using a transmission electron microscope (TEM).

[0050] In the context of the present application, any given numerical value encompasses a range of values from -10% to +10% of the said numerical value, preferably encompasses a range of values from -5% to +5% of the said numerical value, and more preferably encompasses a range of values from -1% to +1% of the said numerical value.

[0051] With reference to the accompanying drawings, further details and advantages of the present invention will become apparent from the following detailed description of several non-limiting embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The present invention will now be described by way of example with reference to the accompanying drawings, wherein:

[0053] Figure 1 is a cross-sectional view illustrating a composite copper foil according to an embodiment of the present invention.

[0054] Figure 2 is illustrative of Figure 1Cross-sectional view of the functional foil.

[0055] Figure 3 Is a graph of intensity (in arbitrary units - CPS) versus binding energy (in electron volts (eV)), showing the results of X-ray photoelectron spectroscopy (XPS) analysis of the Ni region on the surface of the release layer of two composite copper foils produced according to the present invention.

[0056] Figure 4 Is a graph of intensity (in arbitrary units - CPS) versus binding energy (in electron volts (eV)), showing the results of X-ray photoelectron spectroscopy (XPS) analysis of the Ni region on the surface of the release layer of two comparative composite copper foils.

[0057] Figure 5 Is a schematic diagram of a production line for implementing this method. Detailed implementation mode

[0058] Now, the implementation modes of this method and the composite copper foil obtained by this method will be described. For ease of explanation, the composite copper foil will be introduced first.

[0059] Composite copper foil

[0060] Figure 1 Is a cross-sectional view illustrating the composite copper foil 10 that can be obtained by this method.

[0061] The composite copper foil 10 sequentially includes a carrier layer 1, a release layer 2, and an ultra-thin functional layer 3. The carrier layer 1 and the functional layer 3 can also be generally referred to as a carrier foil and a functional foil, respectively. The release layer 2 includes a ternary alloy containing nickel, molybdenum, and tungsten, and is preferably formed as an amorphous layer. The functional foil 3 is an ultra-thin copper foil having a predetermined thickness according to the usage. As Figure 1 As shown by the arrow in, the ultra-thin copper foil 3 can be peeled off from the carrier foil 1, and the separation occurs at the interface with the release layer 2.

[0062] Hereinafter, each layer of the composite copper foil according to an embodiment of the present invention will be described.

[0063] Carrier foil

[0064] According to an embodiment of the present invention, the carrier foil 1 is a support layer for supporting the ultra-thin functional foil 3. The carrier foil 1 acts as a strengthening member or a support for supporting the functional foil 3 until it is bonded to the substrate.

[0065] As is known in the art, the surface roughness of the carrier layer 1 affects the adhesion strength between the ultra-thin copper layer 3 and the resin substrate. For example, when high adhesion strength is required, the surface roughness of the carrier layer 1 is preferably large. On the other hand, when fine circuits need to be formed, the roughness of the carrier layer 1 is preferably small. In one embodiment of the present invention, the surface roughness Rz (JIS) on one side of the carrier layer on which the release layer 2 and the ultra-thin copper foil 3 are formed is preferably 2.5 μm or less, more preferably about 2.0 μm. Although the thickness of the carrier foil 1 is not particularly limited, it is generally sufficient to be self-supporting. For example, considering cost, process, and properties, the carrier foil may have a thickness in the range of 12 - 70 μm.

[0066] Although the material of the carrier layer 1 is not particularly limited, considering cost, process, and properties, copper foil is preferred.

[0067] Release layer

[0068] The release layer 2 is a layer designed to allow the easy release of the functional foil 3 (i.e., the ultra-thin copper foil) from the carrier foil 1. Thanks to the release layer 2, the carrier layer 1 can be easily and neatly detached from the functional foil 3. When the carrier foil 1 and the functional foil 3 are detached from each other, the separation basically occurs at the interface between the release layer 2 and the functional foil 3. That is, the release layer 2 is detached from the functional foil 3 together with the carrier foil 1 and thus remains on the carrier foil 1.

[0069] The release layer 2 comprises a ternary alloy containing nickel, and more preferably the release layer comprises (or consists of) a ternary alloy of nickel, molybdenum, and tungsten. In an embodiment, the ternary alloy layer of the release layer has a Ni content of 1000 - 3000 μg / dm 2 a Mo content of 300 - 1600 μg / dm 2 and a W content of 5 μg / dm 2 or higher. Within the release layer body, Ni, Mo, and W are basically in metallic form. However, it should be noted that the side of the release layer facing / supporting the functional copper foil contains the oxides of the ternary alloy components / elements. The release strength of the surface of the release layer 2 in contact with the ultra-thin copper foil 3 can be controlled by controlling the amount of the oxide.

[0070] The release layer 2 is formed as an amorphous layer, i.e., the alloy of the release layer is preferably an amorphous alloy.

[0071] An amorphous alloy, also known as a non-crystalline alloy, refers to an alloy with an irregular atomic structure like a liquid. Since the peeling layer 2 is amorphous, it is difficult to achieve crystal growth in a specific orientation, and the peeling layer 2 hardly includes grain boundaries. In addition, since the peeling layer 2 is amorphous and has almost no crystal structure even when observed up to the molecular unit, it has higher rigidity and a uniform surface compared to general metal materials. That is, the peeling layer 2 has a smooth surface. The amorphous peeling layer 2 can be formed by any conventional method, for example, vapor deposition method, sputtering method, and plating method, but the plating method is preferably used. Specifically, the wet plating method, that is, the electrodeposition method, is more preferably used.

[0072] The thickness of the peeling layer can vary depending on its preparation method and is not particularly limited, but it is in the range of 30 - 50 nm. However, the thickness of the peeling layer 2 is most preferably in the range of 35 - 50 nm, regardless of the method of forming the peeling layer. In a preferred embodiment, the peeling layer is electroplated on the carrier foil 1, and the thickness of the peeling layer can be adjusted (i.e., controlled) by changing the composition of the electrolyte and electroplating conditions (such as, for example, the current density and temperature of the electrolyte).

[0073] In addition, since the peeling layer 2 is formed in the amorphous alloy layer, the oxide film formed on the peeling layer 2 also has almost no fine irregularities caused by grain boundaries. Therefore, even in the case of the oxide film, a smooth and dense surface can be formed. Thus, pinhole defects can be significantly reduced.

[0074] Functional foil

[0075] The functional copper foil is an ultra-thin copper layer that is intended to be separated from the carrier and retained on the substrate, specifically, to form a copper-clad laminate. In other words, the ultra-thin copper layer (functional foil) can be peeled off from the carrier layer 1 (i.e., can be separated).

[0076] Advantageously, the functional foil is formed by a two-step method and thus includes a first copper layer 4 (or cover layer) and a second copper layer 5, as Figure 2 shown.

[0077] The two layers 4, 5 are formed one on top of the other to obtain a functional foil 3 (or ultra-thin copper foil or ultra-thin copper layer) with the desired thickness. Although formed in two steps, the resulting functional foil 3 is a coherent foil that behaves as a single layer. As mentioned above, the separation from the carrier foil occurs at the interface with the peeling layer, rather than within the functional foil 3. That is, when the carrier foil is separated, the two copper layers 4, 5 do not separate.

[0078] The thickness of the ultra-thin copper layer 3 can vary depending on its manufacturing method and is not particularly limited, but it is in the range of 0.5 - 10 μm. However, regardless of the method of forming the ultra-thin copper layer, the thickness of the ultra-thin copper layer 3 is most preferably in the range of 5 - 9 μm. The method of forming the ultra-thin copper layer 5 is not particularly limited, but the copper layer is preferably produced by electroplating.

[0079] The covering layer 4 is generally a very thin copper or copper alloy layer plated from an alkaline bath. Compared with the body of the functional foil 3, the microstructure of this covering copper layer 4 is very thin to have a more compact and covering layer.

[0080] In a subsequent step, the exposed surface of the ultra-thin copper foil 3 (i.e., the surface opposite to the surface in contact with the release layer) can be subjected to an electrochemical or chemical surface treatment, such as an adhesion enhancement treatment and / or a passivation treatment (not shown).

[0081] Resin layer

[0082] One embodiment of the present invention provides a copper-clad laminate in which a substrate containing a resin is laminated on an ultra-thin copper foil. Herein, the resin of the substrate can be any type of resin as long as the glass transition temperature (Tg) of the resin is lower than the temperature of the lamination process for forming the copper-clad laminate. In an embodiment, the Tg of the resin is lower than 170 °C, preferably lower than 160 °C or lower than 150 °C. The resin of the substrate can include an epoxy-based resin, a polyimide-based resin, a maleimide-based resin, a triazine-based resin, a polyphenylene-based resin, or a polybutadiene-based resin.

[0083] Manufacturing method

[0084] Now, reference will be made to Figure 5 to describe the manufacturing method.

[0085] As described above, the carrier foil can be any suitable self-supporting layer.

[0086] Preferably, the carrier foil 1 is an electrodeposited copper foil. Generally speaking, an electroforming cell 12 (commonly known as a plating machine in the industry) can be used to manufacture the electrodeposited carrier foil in a continuous manner. In the electroforming cell, an electrolyte (an acidic copper bath containing additives) is passed through a device including a cell 18 with a cell inlet 18.1 and a cell outlet 18.2, a rotating drum-shaped cathode 14 (the surface of which is made of stainless steel or titanium), and a fixed anode 16 (a lead or titanium electrode covered with a noble metal oxide) disposed opposite to the cathode. A current is passed through the two electrodes to deposit copper with a desired thickness on the surface of the cathode, thereby forming an electrodeposited copper foil. Then, the electrodeposited copper foil 1 is peeled off from the surface of the cathode 14 and can be wound on a storage reel or directly transferred to the first treatment bath. This method of manufacturing an electrodeposited copper foil is well-known and can be used to manufacture a copper carrier foil suitable for the method of the present invention.

[0087] Depositing the release layer

[0088] A release layer is formed on one side of the electrodeposited copper carrier foil, usually on the drum side. Preferably but not always necessarily, the surface of the carrier layer 1 on which the release layer is formed is pretreated before depositing the release layer 2. The pretreatment method is not particularly limited, and methods such as acid cleaning, alkali degreasing, and electrolytic cleaning are usually used.

[0089] The release layer is preferably formed directly on the surface of the carrier foil by electroplating. Therefore, the carrier foil is guided through a second electroplating bath 20 containing an electrolyte 22 containing nickel, molybdenum, and tungsten and possibly also the required additives, and the carrier foil is placed at the cathode potential.

[0090] The electrolyte for the release layer is usually an acidic aqueous solution.

[0091] Nickel compounds, molybdenum compounds, and tungsten compounds can be used as the sources of nickel, molybdenum, and tungsten respectively. For example, nickel sulfate hydrate can be used as the nickel compound; sodium molybdate or its hydrate, such as molybdenum dihydrate, can be used as the molybdenum compound; tungsten or its hydrate, such as tungsten dihydrate, can be used as the tungsten compound. The solvent of the electrolyte is not particularly limited as long as it is a commonly used solvent, but water is usually used.

[0092] The metal concentration used in the electrolyte bath can be appropriately selected according to the type of metal. For example, in order to form an amorphous alloy layer of Ni, Mo, and W, the Ni concentration is preferably 5 - 9 g / L, more preferably 7.0 - 9.0 g / L, the Mo concentration is 5 - 9 g / L, and the W concentration is 1 - 5 g / L.

[0093] The temperature of the electrolyte is generally in the range of 5 - 70 °C, and preferably in the range of 10 - 50 °C. The current density is generally in the range of 0.2 - 10 A / dm2 within the range of, preferably 0.5 - 5 A / dm 2 range.

[0094] Advantageously, the three metals of the ternary alloy undergo induced codeposition due to the tungsten compound and can thus form an amorphous layer.

[0095] The pH of the electrolyte can vary depending on the metal types of the alloy contained in the release layer. For example, to form a release layer of an alloy including nickel, molybdenum, and tungsten, it is preferred to adjust the pH of the electrolytic bath to 2.0 - 5.0, or for example within the range of 2.5 - 4.5. This is because it is favorable for forming an amorphous alloy layer. When the pH of the electrolytic cell is less than 2.0, a crystalline alloy layer can be formed, while when the pH of the electrolytic cell is greater than 5.0, only a thin film can be obtained because electroplating and precipitation are difficult at such pH values.

[0096] The release layer can be formed in one or more passes, i.e., by a single or multiple electro - deposition steps.

[0097] Regardless of the manufacturing method employed, the release layer is formed to achieve a desired thickness or a specific density (mass per surface unit).

[0098] Cleaning step

[0099] It should be understood that after being formed (i.e., deposited) on the carrier foil, a washing step is performed on the release layer having the desired thickness or specific density. Specifically, the washing step is performed using a washing solution (or rinsing water) having a pH within a specified range.

[0100] The washing solution is generally an aqueous solution. It can have a pH of 2.5 - 4.5, preferably 2.5 - 4.0, more preferably 2.5 - 3.5. For ease of implementation, the washing solution can contain a large amount of water, for example, water in an amount exceeding 90, 95, or 99 wt% relative to the total weight of the washing solution.

[0101] In practice, the washing solution is sprayed onto the exposed surface of the release layer (i.e., onto the surface of the release layer opposite to the surface in contact with the carrier foil) using a nozzle 30. The washing solution can be sprayed onto the release layer in a single step or several times within 10 - 50 seconds. In some embodiments, the washing step is performed in the following order: spraying the washing solution onto the release layer, immersing the carrier foil with the release layer thereon in a bath 32 of the washing solution, and spraying the washing solution onto the release layer leaving the bath.

[0102] This washing step allows the formation of an oxide on the surface of the release layer, which provides the desired release behavior for the low - temperature lamination process.

[0103] After washing, the carrier foil on which the release layer is deposited can be wiped, for example, passed between pressure rollers (such as nip rollers), and then conveyed to a bath for electroplating the functional foil.

[0104] Electrodepositing the functional foil

[0105] As described above, the functional foil is formed in two steps.

[0106] The first copper layer (copper or copper alloy) is formed directly on the release layer, that is, on the washed and dried side of the release layer.

[0107] The first copper layer is formed by electroplating in an alkaline copper plating bath 40. The alkaline bath preferably contains pyrophosphate ions, cyanate ions, and / or sulfamate ions. The current rate is controlled to form a thin, compact, and uniform covering layer. This first / covering copper foil is very thin and is designed as a strike layer to avoid pinholes and promote the deposition of copper at a higher rate.

[0108] Next, using an acidic copper bath 42, usually a copper sulfate bath, a second copper layer is electroplated on the first copper layer. The second copper layer is grown until the desired ultra-thin copper foil thickness is reached.

[0109] Finally, the obtained composite copper foil is rolled onto a receiving drum 50.

[0110] Example

[0111] Composite copper foils are produced using the method according to the invention (Examples) or a comparative method that does not form part of the invention (Comparative Examples). The method according to the invention and the comparative method differ from each other in at least one of the release layer washing step and the release layer deposition conditions.

[0112] For both the Examples and the Comparative Examples, a similar copper foil was used as the carrier foil and pickling was first carried out.

[0113] Then, for both the Examples and the Comparative Examples, an alloy release layer was formed on the carrier layer by electroplating using an electrolyte comprising nickel (Ni), molybdenum (Mo), and tungsten (W). Table 1 lists the amounts of Ni, Mo, and W in the respective baths. An electrolyte with a pH of 2 - 5 and a temperature of 15 - 60 °C was used, and a current density of 0.8 - 8 A / dm 2 was applied for the deposition of the release layer. The release layer of the foil according to the Examples was washed with a washing solution having a pH of 2.5 - 4.5 to oxidize the surface and form an oxide. The release layer of the foil according to some Comparative Examples was also washed with a washing solution having a pH of 2.5 - 5.0.

[0114] Table 1 lists the pH of the respective washing solutions for the foils according to the invention and, if appropriate, for the comparative foils.

[0115] In practice, the washing step is carried out as follows: when emerging from the electrolyte bath for stripping, the carrier foil supporting the stripping layer is sprayed with the washing liquid, immersed in a washing liquid bath, and further sprayed with the washing liquid thereon, and then it enters the next electroplating bath for ultra-thin copper foils.

[0116] The plating of the ultra-thin copper foil is completed in two steps. First, a covering layer is plated onto the stripping layer (i.e., on its washed / oxidized surface) using an alkaline plating bath to form a very thin continuous covering layer.

[0117] Then, a second copper layer is plated onto the first layer using an acidic copper sulfate bath to a thickness required to obtain the desired ultra-thin copper foil thickness.

[0118] Table 1 gives the main distinguishing features of the composite copper foils according to the invention and the comparative embodiments.

[0119] Then the obtained composite copper foils (according to the invention and the comparative examples) are laminated onto a substrate, and the peel strength is measured.

[0120] The lamination process and the peel strength measurement are well known in the art and are briefly described below only.

[0121] Laminating process

[0122] To determine the behavior of the foils during lamination, they are laminated at 170 °C: the composite copper foils are laminated onto epoxy resin FR4 at 170 °C for 1 hour.

[0123] Peel strength measurement

[0124] The peel strength (or release strength) between the carrier and the ultra-thin copper foil is measured at 90°. The test is carried out according to the IPC-TM-650 method 2.4.8.5. The peel strength values are shown in Table 1.

[0125] It is clear from Table 1 that for all the composite copper foils according to the invention (Examples 1-4), after lamination at 170 °C for 1 hour, the peel strength is 30 - 120 N / m. The composite copper foils of the invention can be peeled within the conventional peel force after low-temperature lamination. Thus, the carrier layer of the composite copper foils produced according to the invention still adheres to the ultra-thin copper layer after lamination at 170 °C, with a peel strength of 30 - 120 N / m. Before peeling the carrier layer, the copper layer can be further processed (drilling, …).

[0126] [Table 1]

[0127]

[0128]

[0129] In contrast, in the absence of a washing step (comparative Examples 1 and 2), after the composite copper foil was laminated at 170 °C for 1 hour, the peel strength was less than 5 N / m, which means that the carrier foil was too easily peeled off after lamination. The carrier foil could not play a protective role during different subsequent manufacturing steps of the printed circuit board, and the ultra-thin copper foil could not be further processed. In other words, the composite foils of Comparative Examples 1 and 2 were not suitable for the low-temperature lamination process.

[0130] And when the washing step was carried out using a washing solution with a pH of 5.0, that is, outside the specified range, the peel strength became too high, which means that the ultra-thin copper foil became unable to be peeled off from the carrier foil.

[0131] In addition, when depositing the release layer using an acidic electrolyte containing Ni, Mo, or W outside the specified range (for example, more Ni - Comparative Example 3, less W - Comparative Example 4, or less Mo - Comparative Example 5), although the peel strength was much higher than that of Comparative Examples 1 and 2 and was sufficient to ensure the cohesion of the composite copper foil during its subsequent manufacturing steps, it was still not as high as that of the copper foil of the present invention and was less than 30 N / m.

[0132] As a further comparison, the composite copper foil of the present invention was subjected to high-temperature lamination (2 hours at 220 °C) and became non-peelable, while the composite copper foil of Comparative Example 1 exhibited a peel strength of 15 N / m.

[0133] Therefore, only the production method of the composite copper foil corresponding to the present invention, that is, including depositing the release layer using an acidic electrolyte containing Ni, Mo, and W at a specified concentration and including the step of cleaning the release layer before depositing the ultra-thin copper foil, can manufacture a composite copper foil having a high peel strength suitable for low-temperature lamination.

[0134] To further characterize the different composite copper foils, after peeling off the functional foil, X-ray photoelectron spectroscopy (XPS) measurements were carried out on the surface of the release layer. In the nickel (Ni) region, the binding energies of the composite copper foils according to the present invention ( Figure 3 - Examples 1 and 2) and the composite copper foils according to the comparative examples ( Figure 4 - Comparative Examples 1 and 2) were measured.

[0135] As can be observed, for the release layers of the examples and comparative examples, nickel was mainly metallic, and the oxidized nickel was mainly in the +II oxidation state. Ni 2+ was mainly in the form of oxides or hydroxides. As Figure 3 shown, compared with the comparative examples ( Figure 4)Compared with [reference], the amount of Ni(+II) on the surface of the release layer in the example is more important, that is, its sample has a higher release strength.

Claims

1. A method for producing a composite copper foil comprising a carrier foil, a release layer, and an ultra-thin copper foil, wherein the ultra-thin copper foil can be peeled off from the carrier foil, the method comprising: - providing a carrier foil; - depositing a release layer of a ternary alloy comprising nickel, molybdenum, and tungsten on the carrier foil using an acidic electrolyte comprising nickel, molybdenum, and tungsten, the release layer being an amorphous layer; - washing the exposed side of the release layer on the carrier foil with a washing solution having a pH of 2.5 - 4.5; - electroplating an ultra-thin copper foil on the release layer.

2. The method according to claim 1, wherein the pH of the washing solution is 2.5 - 4.0, preferably 2.5 - 3.

5.

3. The method according to claim 1 or 2, wherein the washing solution comprises water and an acid, preferably an inorganic acid.

4. The method according to any one of the preceding claims, wherein washing the exposed side of the release layer comprises spraying the washing solution and / or immersing it in the washing solution.

5. The method according to any one of the preceding claims, wherein washing the exposed side of the release layer is carried out for a period of 10 - 50 seconds, preferably 10 - 30 seconds.

6. The method according to any one of the preceding claims, wherein the washed release layer is placed in air for 10 - 40 seconds.

7. The method according to any one of the preceding claims, wherein the acidic electrolyte comprises nickel at a concentration of 5.0 - 9.0 g / L, preferably 7.0 - 9.0 g / L, more preferably 7.5 - 8.5 g / L, molybdenum at a concentration of 5.0 - 9.0 g / L, preferably 5.0 - 7.0 g / L, more preferably 5.5 - 6.5 g / L, and tungsten at a concentration of 1.0 - 5.0 g / L, preferably 2.0 - 4.0 g / L, more preferably 2.5 - 3.5 g / L.

8. The method according to any one of the preceding claims, wherein electroplating the ultra-thin copper foil comprises: electroplating a first copper layer directly on the release layer using an alkaline copper electrolyte; and electroplating a second copper layer on the first copper layer using an acidic copper electrolyte.

9. The method according to claim 8, wherein the alkaline bath preferably comprises pyrophosphate ions, cyanate ions, and / or sulfamate ions.

10. A composite copper foil comprising, in order, a carrier foil, a release layer, and an ultra-thin copper foil, wherein the release layer comprises a ternary alloy of nickel, molybdenum, and tungsten formed as an amorphous layer, and wherein the release strength of the release layer after lamination at 170 °C for 1 hour is 30 - 120 N / m.

11. The composite copper foil according to claim 10, wherein the release layer comprises an oxide form of the ternary alloy comprised in the release layer at its interface with the functional foil.

12. The composite copper foil according to claim 10 or 11, wherein at the interface with the ultra-thin copper foil, the release layer comprises an oxide form of nickel, wherein nickel having a +II oxidation state accounts for at least 30 wt% of the total nickel on the surface.

13. The composite copper foil according to any one of claims 10 - 12, wherein the release layer has a thickness of 5 - 50 nm, preferably 30 - 50 nm, more preferably 35 - 50 nm.

14. The composite copper foil according to any one of claims 10 - 13, wherein the thickness of the ultra-thin copper foil is 5.0 - 9.0 μm.

15. The composite copper foil according to any one of claims 10 - 14, wherein the composite copper foil is produced by using the method according to any one of claims 1 - 9.

16. A copper-clad laminate, comprising a substrate having a resin and the composite copper foil according to any one of claims 10 - 15, the ultra-thin copper foil being laminated on the exposed surface of the substrate, wherein the resin of the substrate has a Tg lower than 170 °C, and Among them, the peel strength of the composite copper foil after lamination at 170 °C for 1 hour is 30 - 120 N / m.

Citation Information

Patent Citations

  • Thin foil

    US3998601A

  • Composite copper foil and method of fabricating the same

    WO2020173574A1